2013
DOI: 10.1021/jo4001349
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an σ-Alkyl Iridium Hydride Complex, Formed in the (Semi)hydrogenation of an β-Enamido Ketone

Abstract: σ-Alkyl iridium hydride complexes are generally postulated as intermediates in iridium-catalyzed hydrogenation. Fast reductive elimination results in the formation of the hydrogenation product. With an β-enamido ketone as unsaturated substrate, such an intermediate could be trapped because the semihydrogenated product coordinates trifold to the iridium, generating a stable 18e(-) complex, which does not eliminate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The Burgess group proposed a model involving the chelation of the carbonyl group to the Ir metal center and in following studies several pathways involving a chelation were suggested to explain the enantioselective outcome obtained from a,b-unsaturated molecules. [68][69][70] In 2016, Bolm and co-workers investigated the mechanism of the hydrogenation of a,b-unsaturated ketones using an Iridium sulfoximine catalyst by means of DFT studies. Substrate chelation was proposed in this case as well and, in contrast with previous studies, the coordination of the olefin was proposed to be trans to the ligand nitrogen atom.…”
Section: Enantiodivergencementioning
confidence: 99%
“…The Burgess group proposed a model involving the chelation of the carbonyl group to the Ir metal center and in following studies several pathways involving a chelation were suggested to explain the enantioselective outcome obtained from a,b-unsaturated molecules. [68][69][70] In 2016, Bolm and co-workers investigated the mechanism of the hydrogenation of a,b-unsaturated ketones using an Iridium sulfoximine catalyst by means of DFT studies. Substrate chelation was proposed in this case as well and, in contrast with previous studies, the coordination of the olefin was proposed to be trans to the ligand nitrogen atom.…”
Section: Enantiodivergencementioning
confidence: 99%
“…Kazmaier and Maurer isolated a σ‐alkyl iridium complex, which was suggested to be a possible intermediate in the hydrogenation of β‐enamido ketones with an iridium phosphinite oxazoline catalyst . Probably general for related complexes of this type, the compound showed a keto‐to‐Ir coordination.…”
Section: Introductionmentioning
confidence: 99%